Evolution, Transposition, Transformation and Flow of Information - Vitas, Marko; Dobovišek, Andrej (Anali PAZU, 2022)
Modern science has still not given us a satisfactory empirical explanation of the increasing complexity in living beings through evolutionary history, though whether or not the complexity increases in biological evolution is a hotly debated topic and no agreed-upon definitions of the complexity exist. Nevertheless, this poses the question when comparing simple prokaryotic cells with more complex eukaryotic cells or comparing these with animals or plants or the most complex phenomena, e.g. consciousness and human language. The question of how life actually came into existence is definitely important in this respect. Assuming the hypothesis that in the beginning of the origins of life evolution had to first involve autocatalytic systems which only subsequently acquired the capacity of genetic heredity, we discuss in the present article the possible emergence of digital, discrete information arising from analogue information stored in the intra and intermolecular interactions throughout the molecular evolution. Explaining the origin of life is perhaps central and the most challenging question in modern science. The results of such debates and investigations might shift current biological paradigms and might also have a momentous significance for modern philosophy in understanding our place in universe.
Keywords: origin of life; information; chemical evolution; complexity; genetic code; recombination